Proyecto de factibilidad para la creación de una empresa productora y comercializadora de miel de coco en la ciudad de Loja, provincia de Loja. - Coronel Chamba, Jaime Andres (2024)
The present Curricular Integration Work, "Feasibility Project for the Establishment of a Coconut Honey Trading Company in the City of Loja," aims to determine the feasibility of creating a coconut honey trading company in the city of Loja, with the main objective of establishing the technical, economic, and financial viability that guarantees its implementation. The project's development began with a feasibility study, including a market study that determined an effective demand of 97% based on the conducted survey. In the Technical Study, a Macro and Micro location matrix indicated that the company would have its commercial address in the "Pucacocha" neighborhood, El Valle parish, and Loja canton, Loja province. This location was chosen primarily for its accessibility advantages for vehicles of any type, being next to the 8 de diciembre Avenue, providing future customers with the necessary space and characteristics for product acquisition, in addition to being a commercially vibrant area. Financial evaluation revealed a positive Net Present Value (NPV) of $64,912.34 and an Internal Rate of Return (IRR) of 90.21%. The Benefit-Cost Ratio yielded a positive value of $1.56, signifying that for every dollar invested, there will be a profit of $0.56. Regarding the Payback Period (PRC), the project is projected to recover the investment of $89,662.16 in 3 years, 7 months, and 19 days, considered an acceptable period. Finally, Sensitivity Analysis determined that the project can withstand a 77.80% increase in costs and a 10.70% decrease in revenues. In conclusion, considering the positive financial evaluation indicators ensuring profitability, the creation of the company is deemed feasible. Therefore, its execution is recommended.